1991
DOI: 10.1038/bjc.1991.482
|View full text |Cite
|
Sign up to set email alerts
|

Molecular monitoring of low grade non-Hodgkin's lymphoma by gene amplification

Abstract: Molecular monitoring by the polymerase chain reaction was used to detect and follow minimal disease in working formulation category B and C on non-Hodgkin's lymphoma. Rearrangement of the bcl-2 gene served as the target for gene amplification. Thirty patients were studied. Bone marrow histology was compared to PCR analysis of bone marrow aspirate and blood. PCR upstaged disease status in approximately 50% of patients. Results are shown from a patient whose disease was followed with PCR during chemotherapy from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Therefore, it may reduce the need for more invasive examinations. Similar results, with a lesser degree of concordance between bone marrow and peripheral blood analysis, have recently been published (Hickish et al, 1991) indicating the PCR can be an effective means for clinical monitoring of low-grade lymphomas. However, the clinical significance of detecting minimal disease in bone marrow by PCR has still to be established and will require prolonged follow-up because of the natural history of FL with a median survival than can exceed 8 years in advanced stages.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, it may reduce the need for more invasive examinations. Similar results, with a lesser degree of concordance between bone marrow and peripheral blood analysis, have recently been published (Hickish et al, 1991) indicating the PCR can be an effective means for clinical monitoring of low-grade lymphomas. However, the clinical significance of detecting minimal disease in bone marrow by PCR has still to be established and will require prolonged follow-up because of the natural history of FL with a median survival than can exceed 8 years in advanced stages.…”
Section: Discussionsupporting
confidence: 64%
“…This technique can detect one lymphoma cell in a background of 10 6 normal cells. Similar evidence for the presence of PCR-detectable occult disease in the presence of histologically normal marrow has been reported from other centers [11,12,21,22,23]. Considering the studies of genetically marked autologous marrow cells, which suggest that reinfused tumor cells contribute to relapse [24,25], in a disease such as follicular NHL several approaches have been taken to provide a tumor-free stem cell preparation.…”
Section: Problems With Myeloablative Therapy In Follicular Lymphomasmentioning
confidence: 58%
“…PCR amplifications at the major and minor breakpoint regions of the bcl-2 translocation or IgH locus were performed using nested oligonucleotides as described elsewhere [21]. In samples with no detectable PCR product, PCR amplification was repeated using oligonucleotide primers specific for the V region of the gene encoding the human B-cell activation antigen B7 and confirmed that PCR-amplifiable DNA was present in each of the samples analyzed.…”
Section: Pcrmentioning
confidence: 99%